Eliza Calvert Hall : Kentucky Author and Suffragist. - Niedermeier, Lynn E. (The University Press of Kentucky, 2015)
In 1907, the author, poet, essayist, and folk art historian Eliza Calvert Hall (1856--1935) published Aunt Jane of Kentucky, a collection of stories about rural life infused with the spirit and gentle good humor of its elderly narrator, Aunt Jane. The book and several sequels achieved wide popularity and placed Hall in the front ranks of ""local color"" fiction writers of her time. As Hall struggled to balance her writing career with the duties of a nineteenth-century wife and mother, suffragist Laura Clay was lobbying for every woman's right to vote. Hall joined the battle, writing fearlessl.